2012
DOI: 10.1097/brs.0b013e318245f561
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Causes of Readmission After Spine Surgery

Abstract: Infection, medical complications after surgery, and surgical complications requiring revision of implants are the primary causes of unplanned early readmissions and spine surgery. Further studies are necessary to identify patients and procedures most associated with readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
74
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 23 publications
9
74
0
1
Order By: Relevance
“…11 McCormack reported 30 day unplanned readmission rates of 4.3% for anterior cervical spine fusion patients and 5.9% for posterior cervical fusion patients from 2007 through 2009. 7 His study is of particular interest because it took place at the same institution as ours, yet it reported higher readmission rates than we observed from 2011 through 2014. These disparate findings can be explained, at least in part, by changes in institution protocol that included application of intrawound vancomycin powder in posterior cervical surgeries, (b) routine nasal swabbing for identification of Staphylococcus carriers in order to optimize antibiotic prophylaxis and (c) standardization of dressing protocol.…”
Section: Discussionmentioning
confidence: 37%
See 2 more Smart Citations
“…11 McCormack reported 30 day unplanned readmission rates of 4.3% for anterior cervical spine fusion patients and 5.9% for posterior cervical fusion patients from 2007 through 2009. 7 His study is of particular interest because it took place at the same institution as ours, yet it reported higher readmission rates than we observed from 2011 through 2014. These disparate findings can be explained, at least in part, by changes in institution protocol that included application of intrawound vancomycin powder in posterior cervical surgeries, (b) routine nasal swabbing for identification of Staphylococcus carriers in order to optimize antibiotic prophylaxis and (c) standardization of dressing protocol.…”
Section: Discussionmentioning
confidence: 37%
“…King et al 6 and McCormack et al 7 have reported higher readmission rates after posterior approach surgery when compared to anterior approach. This is consistent with findings in our cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is low compared with other orthopaedic studies [9,27]. As we would expect with a low incidence of surgical readmission, our medical 30-day readmission rate of 42% is high when compared with other studies [18,20,23]. The most common cause of surgical readmission is surgical site infection.…”
Section: Discussionmentioning
confidence: 50%
“…In analyzing the variable of interest of this review, meaning the readmission characteristics from orthopedic surgical site infection, it was found that the objectives of included publications varied between characterizing unplanned readmissions within 30 days after discharge (20)(21)(22)(23) , identifying predictors of surgical readmission within 30 days in overall readmission rates (24) , assessing their impact on costs, average stay and overall readmission rates, as well as its causes and risk factors (20)(21)(25)(26) and associated comorbidities (27) . Studies analyzing the impact of seasonality (28) and influence of goals and educational video programs on events that also included readmission (29) were also performed.…”
Section: Discussionmentioning
confidence: 99%